Answer:
[tex]k = -0.1733[/tex]
Step-by-step explanation:
The first step to solve this equation is placing everything with the exponential to one side of the equality, and everything without the exponential to the other side. So
[tex]24e^{4k} = 12[/tex]
[tex]e^{4k} = \frac{12}{24}[/tex]
The ln is the interse operation to the exponential, so we apply the ln to both sides of the equality.
[tex]\ln{e^{4k}} = \ln{\frac{12}{24}}[/tex]
[tex]4k = -0.6931[/tex]
[tex]k = -\frac{0.6931}{4}[/tex]
[tex]k = -0.1733[/tex]